2017
DOI: 10.3389/fimmu.2017.01553
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Strain Lactobacillus casei BL23 Prevents Colitis-Associated Colorectal Cancer

Abstract: The gut microbiota plays a major role in intestinal health, and an imbalance in its composition can lead to chronic gut inflammation and a predisposition to developing colorectal cancer (CRC). Currently, the use of probiotic bacteria represents an emerging alternative to treat and prevent cancer. Moreover, consumption of these beneficial bacteria may also favorably modulate the composition of the gut microbiota, which has been described in several studies to play an important role in CRC carcinogenesis. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(109 citation statements)
references
References 32 publications
1
101
0
1
Order By: Relevance
“…On the other hand, genus Lactobacillus and genus Enterococcus, were overrepresented in healthy tissues in the current study, which have been long regarded as anti-inflammation and anti-tumorigenic probiotics [28,29]. A recent study also reported that genus Lactobacillus was able to counterbalance the dysbiosis induced by CRC in human and mice [26,30]. In an animal study, genus Enterococcus was shown to inhibit chemically-induced CRC [31].…”
Section: Discussionmentioning
confidence: 44%
“…On the other hand, genus Lactobacillus and genus Enterococcus, were overrepresented in healthy tissues in the current study, which have been long regarded as anti-inflammation and anti-tumorigenic probiotics [28,29]. A recent study also reported that genus Lactobacillus was able to counterbalance the dysbiosis induced by CRC in human and mice [26,30]. In an animal study, genus Enterococcus was shown to inhibit chemically-induced CRC [31].…”
Section: Discussionmentioning
confidence: 44%
“…As known butyrate producers, Clostridium butyricum and Bacillus subtilis could inhibit DMH‐induced colonic tumor in mice . Notably, another probiotic, Lactobacillus casei strain BL23 not only inhibited CRC in mice, but also counteracted gut dysbiosis induced by CRC . Additionally, recent clinical studies established that oral Bifidobacterium triple viable probiotics could improve gut dysbiosis and combat small intestinal bacterial overgrowth in CRC patients …”
Section: Fmt As a Possible Therapy For Various Type Of Cancers And Camentioning
confidence: 99%
“…87 Notably, another probiotic, Lactobacillus casei strain BL23 not only inhibited CRC in mice, but also counteracted gut dysbiosis induced by CRC. 88 Additionally, recent clinical studies established that oral Bifidobacterium triple viable probiotics could improve gut dysbiosis and combat small intestinal bacterial overgrowth in CRC patients. 89,90 Our team identified the role of intestinal dysbiosis induced by deoxycholic acid (a carcinogenic secondary bile acid) in the development of CRC.…”
Section: Fmt For Digestive System Cancersmentioning
confidence: 99%
“…W badaniu na modelu zwierzęcym Jacouton i wsp. wykazano, że szczep Lactobacillus casei BL23 zapobiega rozwinięciu raka jelita grubego, ponieważ posiada właściwości immunomodulujące (obniża stężenie interleukiny przeciwzapalnej -IL-22), a także wywiera efekt antyproliferacyjny, regulując kaspazy (7 i 9) oraz białko proapoptyczne Bik [28].…”
Section: Probiotyki a Rak Jelita Grubegounclassified